Beyond neurodegenerative diseases: α-synuclein in erythropoiesis - Ling Ling; Fangfang Wang; Duonan Yu (Hematology, 2022)
α-synuclein (α-syn) is a highly conserved and thermostable protein that is widely distributed in human brain. An intracellular aggregation of α-syn in dopaminergic neurons is the hallmark of a group of neurodegenerative diseases including Parkinson’s disease. Interestingly, α-syn is also highly expressed in red blood cells and is considered as one of the most abundant proteins in red blood cells. Moreover, α-syn is thought to play a regulatory role during normal erythropoiesis. However, whether α-syn participates in the pathogenesis of erythroid diseases has not been reported. In this review, we discuss the protein structure of α-syn and the importance of α-syn in erythropoiesis.